Applications of natural polysaccharide-based pH-sensitive films in food packaging: Current research and future trends. (December 2022) - Li, Nan; Zhou, Siyu; Yang, Xingbin; Lin, Dehui
Abstract: With the increased awareness of food safety and growing environmental concern of plastic packaging disposal, the research and development of novel food packaging is extremely urgent and attracts much attention. Natural polysaccharides are ideal candidate materials to develop "green" food packaging due to their biodegradable properties and good film-forming properties. Especially, the natural polysaccharides-based intelligent films can provide consumers the real-time information about the quality and safety of the packaged food through the pH-sensitive indicators. Consequently, this paper summarized the current researches on the development of natural polysaccharides-based pH-sensitive films. Then, the applications of natural polysaccharides-based pH-sensitive films in food packaging, including the packaging for meat products, fruits and vegetables, etc., are emphasized. Finally, an overview of the trends/challenges of pH-sensitive films in food packaging is discussed. Taken together, the natural polysaccharide-based pH-sensitive food packaging films show more advantages as compared with the common food package films, which can not only protect the packaged food, but also monitor the quality of packaged food in real time. Nevertheless, the further studies should continue to focus on the commercially sustainable key points including consumer acceptance and trust, cost, regulatory considerations and multifunctional performance of the pH-sensitive food packaging films. Graphical abstract: Unlabelled Image Highlights: Carbohydrate polymer-based films incorporated with pH-sensing pigments are summarized. The application of pH-sensing films in food packaging is emphasized. PH-sensing films provide consumers the real-time information of the packaged food. Carbohydrate polymer-based pH-sensing films have great potential in food packaging field.